Strategic responsiveness and adaptive organisations : new research frontiers in international strategic management - Andersen, Torben Juul; Torp, Simon; Linder, Stefan (Emerald studies in global strategic responsiveness, 2019)
This volume of the Emerald Studies in Global Strategic Responsiveness presents a selection of articles from the EURAM 2018 conference. They offer a range of new promising approaches about how to deal with the strategic challenges associated with contemporary market turbulence and the increasingly unpredictable business conditions.